2020
DOI: 10.1371/journal.pone.0230892
|View full text |Cite|
|
Sign up to set email alerts
|

The Maya Preclassic to Classic transition observed through faunal trends from Ceibal, Guatemala

Abstract: It is well known that the development of the ancient Maya civilization had significant and long-lasting impacts on the environment. This study assesses a large collection of faunal remains (>35,000 specimens) recovered over a span of several kilometers in and around the archaeological site of Ceibal, Guatemala, in order to determine whether the composition of animal resources was continuous throughout the site's history between 1000 BC and AD 1200, or whether there were any changes that could be attributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…The partial antlers found with two burials reflect a widespread Maya funerary practice spanning the Late Preclassic through Classic period. Remains of worked and unworked antlers have been found in human burials from Caracol (Teeter 2004) and Cahal Pech (Awe 2013) in Belize, Ceibal (Sharpe et al 2020) in Guatemala, and Copan (Sugiyama et al 2019) in Honduras. They may have been ornamental objects, including headdresses.…”
Section: Discussionmentioning
confidence: 99%
“…The partial antlers found with two burials reflect a widespread Maya funerary practice spanning the Late Preclassic through Classic period. Remains of worked and unworked antlers have been found in human burials from Caracol (Teeter 2004) and Cahal Pech (Awe 2013) in Belize, Ceibal (Sharpe et al 2020) in Guatemala, and Copan (Sugiyama et al 2019) in Honduras. They may have been ornamental objects, including headdresses.…”
Section: Discussionmentioning
confidence: 99%
“…Other ancestral Maya sites near floodplains, lagoons, and rivers present evidence for aquatic resource consumption (Sharpe et al 2020) and human-modified waterscapes for fish (Harrison-Buck et al 2020), like at Edzna and Pulltrouser Swamp mentioned above. Investigators examining nitrogen isotopic levels from bone collagen from Classic Maya human burials, for instance, have additionally shown that cities near large rivers often utilized freshwater fish (Scherer et al 2007:97).…”
Section: Integrated Subsistence: Fish In the Maya Dietmentioning
confidence: 96%
“…Comparative evidence for the importance of freshwater fish, in addition to other aquatic species such as turtles, waterfowl, and mollusks, has been presented from archaeology, historic documents, and ethnographies across the Maya region (Harrison-Buck et al 2020;Ruz 1998;Sharpe et al 2020;Thompson 1974). For instance, through excavations and ethnography, Dillon (1981) indicates that Classic-period Maya at Camelá near the Chixoy River in lowland Guatemala could not have raised many crops in the swampy terrain around a large lagoon.…”
Section: Integrated Subsistence: Fish In the Maya Dietmentioning
confidence: 99%
“…Examination of the role of pocket gophers in Classic period Maya art has led Stone et al (2011:81-82) to suggest they may have been used as pets, since they are depicted in the arms of individuals or seated nearby. While gopher bones are occasionally found at Maya sites (e.g., Boileau and Stanchly 2020; Sharpe et al 2020;Wing 1981), the rarity of their remains indicates they were not a common staple. Gophers are hunted today in the Maya area such as the Quintana Roo region where snare traps are placed near burrows (Hovey and Rissolo 1999).…”
Section: Closer Examination Of Potentially Non-local Gophersmentioning
confidence: 99%